Model Pembelajaran Value Clarification Technique (VCT) Berbantuan Media Prezi terhadap Sikap Sosial Peserta Didik pada Pembelajaran IPAS Kelas IV SD - P.F, Bunga Adelia; Erni, Erni; Perdana, Dayu Rika; Sowiyah, Sowiyah (Innovative: Journal Of Social Science Research, 2025)
The problem of this research is the low social attitudes of fourth-grade students in elementary school. The purpose of the research is to determine the positive impact of the Value Clarification Technique (VCT) learning model assisted by Prezi media on social attitudes in the IPAS learning of fourth-grade students in elementary school. The research method used is quantitative research with a quasi-experimental method, and the research design uses a pretest-posttest control group design. The population and sample of the study are all fourth-grade students of SD Negeri 3 Jatimulyo, Lampung Selatan, totaling 61 students. The sampling technique used in this study is the saturated sampling technique. The data analysis technique uses simple regression testing. The results of the study show that there is an effect of the application of the Value Clarification Technique learning model assisted by Prezi media on the social attitudes of students in IPAS learning for fourth-grade students at SD Negeri 3 Jatimulyo for the 2024/2025 academic year.